H1N1 Influenza: Epidemiology, Surveillance, and Laboratory Diagnosis—Implications for Public Health Practice - AlMaliki, Mohammed Awadh; Yasser Ali Abdu Doshi; Ahmed Abduh Ahmed Hamzi; Adeeb Abdullatif Alshuwaier; Ali Mohammed Shrahili; Mohammed Abdullah Almarshud; Nayef Mansour Al-Shaitan; Jabril Yousef Ahmed Abdali; Mohammed Ahmad Othman Naseeb; Mohammad Abdullah M Alrehaili (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> H1N1 influenza, a subtype of influenza A virus, is a highly transmissible respiratory illness with pandemic potential. Its emergence in 2009 highlighted the interplay between viral evolution, zoonotic transmission, and global public health preparedness. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the epidemiology, virology, clinical features, diagnostic strategies, and management of H1N1 influenza, emphasizing implications for surveillance and prevention. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature-based analysis was conducted, synthesizing historical data, virologic characteristics, epidemiologic patterns, and clinical management strategies documented during the 2009 pandemic and subsequent outbreaks. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> H1N1 influenza demonstrates genetic plasticity through antigenic drift and shift, enabling reassortment across swine, avian, and human hosts. The 2009 pandemic infected up to 24% of the global population, causing an estimated 151,700–575,500 deaths. Clinical presentation ranges from mild upper respiratory illness to severe viral pneumonia and ARDS, with complications including bacterial superinfection and multisystem involvement. Laboratory confirmation relies on RT-PCR, supported by serology and culture. Early antiviral therapy with neuraminidase inhibitors significantly reduces morbidity and mortality, while vaccination remains the cornerstone of prevention. Integrated “One Health” surveillance and occupational risk mitigation are essential to limit zoonotic spillover and pandemic emergence. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> H1N1 influenza exemplifies the dynamic nature of influenza epidemiology and underscores the need for coordinated global strategies encompassing surveillance, vaccination, and timely antiviral intervention to reduce disease burden and prevent future pandemics.